Encryption of Walsh Hadamard Transform applied images with the AES encryption algorithm - Kurt Pehlivanoglu, Meltem; Duru, Nevcihan (2016 24th Signal Processing and Communication Application Conference (SIU), 2016)
Developing technology threaten to the information security and privacy. Today, for data transfer in a private and secure environment, the use of encryption methods or cryptographic systems are inevitable. In this study WHT (Walsh-Hadamard Transform) that is used, one of the transforms that used image processing techniques such as attribute extraction on image files, text analysis, filtering, compression. Image pixel values obtained at the end of transformation encrypt with AES (Advanced Encryption Standard) encryption algorithm. Using encryption pixel values encrypted txt file was obtained.